O tak zwanym szpiegu i terroryście koronnym - Hoc, Stanisław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The subject of this article is the authorization of intelligence services in preventing and combating the offences of espionage and terrorism. It describes the regulations of the Second Polish Republic regarding espionage, a draft Act on Intelligence Activities, the rule of law and opportunism, and most importantly new regulations under the anti-terrorism law.
Keywords: bezpieczeństwo państwa; legalizacja dokumentów; przestępstwo terrorystyczne; szpiegostwo